Do we have Policies on Dealing with Problem Pay Rates? - Binghay, Virgel C. (Philippine Journal of Labor and Industrial Relations; Vol 37 (2020): Philippine Journal of Labor and Industrial Relations, 2023)
Despite having a sound pay structure, problem pay rates (PPR) could still occur. This happens when an employee’s pay is over or under the intended amount based on the company’s pay structure. These so-called PPRs are called red circle and green circle pay rates (RCPR/GCPR). Policies designed for PPRs and the appeal policy procedures (APP) are crucial in preventing or minimizing pay issues. However, in the Philippines, there is a shortage of data on the subject. Hence, this study aims to determine if companies maintain policies relative to addressing PPRs and if they have an APP to handle attendant conflicts and issues. This seminal study employed a two-part survey comprised of 148 respondents from different companies. It was found that said policies are present in only a few companies. Hence, this study suggests that more companies adopt and maintain these policies for sound compensation management. In this study, the companies are categorized in terms of ownership type, industry affiliation, workforce size, and business location.